The Relationship Between Psychological Contract Breach and Employees’ Counterproductive Work Behaviors: The Mediating Effect of Organizational Cynicism and Work Alienation - Li, Shuang; Chen, Yang (Frontiers in Psychology, 2018)
Psychological contract breach (PCB) may trigger negative attitudes in employees and ultimately cause further negative behaviors. By drawing on social exchange theory, this study aims to explore the link between PCB and counterproductive work behavior (CWB) by focusing on the mediating role of organizational cynicism and work alienation. We administered a cross-sectional survey of 484 energy company front-line employees. The conceptual model was examined via structural equation modeling. The results suggested that organizational cynicism and work alienation sequentially mediated the relationship between PCB and CWB. This study elucidated the mechanisms underlying the relationship between PCB and CWB by introducing negative attitudes (i.e., organizational cynicism and work alienation) into the model, and offered further evidence that organizations should pay more attention to employees’ PCB and negative attitudes in order to reduce their CWB. Keywords: psychological contract breach, organizational cynicism, work alienation, counterproductive work behavior, mediating effect.